Efeitos cardiovasculares da Hidroxicloroquina em animais normotensos e hipertensos - Costa, Jaqueline Moura da (2025)
Hydroxychloroquine (HCQ) is widely used for the treatment of rheumatic diseases. Studies show that patients using this medication may experience cardiovascular and metabolic alterations. On the other hand, studies indicate that HCQ may have protective effects on the heart and metabolism. However, there are not many studies evaluating its effects under hypertensive conditions. Thus, the present study aimed to evaluate the cardiovascular effects of HCQ and whether these effects differ in hypertensive animals. Male normotensive (Wistar) and hypertensive (SHR, spontaneously hypertensive rats) rats, aged 16 weeks, were used. The experimental groups were divided into Wistar vehicle, Wistar HCQ, SHR vehicle, and SHR HCQ groups. The animals received either saline or HCQ (40 mg/kg/day) via gavage for 30 days. Body weight, water and food intake, systolic blood pressure (SBP), and heart rate (HR) were assessed weekly. SBP and HR were analyzed using tail-cuff plethysmography. Cardiac contractility was evaluated using the isolated heart technique under constant pressure. Aortic reactivity was assessed in isolated aortic rings using an organ bath system. The following organs were collected for weighing and/or histological and molecular analysis: left ventricle (LV), liver, pancreas, and white and brown adipose tissues. Normotensive animals treated with HCQ exhibited reduced body weight during the last two weeks of treatment compared to basal and the vehicle group at the same time. Both treated and untreated hypertensive animals showed a similar increase in body weight. The Wistar rats treated with HCQ consumed less feed and water than their control group, and there was a reduction in water intake in SHR. HCQ treatment did not significantly alter SBP in either strain; however, it increased HR in Wistar rats. Left ventricular function and coronary and aortic reactivity were not affected by HCQ. The ventricular mass index (VMI) was lower in Wistar HCQ rats, and cardiomyocyte diameter was reduced in both normotensive and hypertensive treated rats. HCQ did not alter the expression or phosphorylation of ERK1/2 or the activity of matrix metalloproteinase 2 in either strain. Superoxide dismutase (SOD) and catalase (CAT) expression was higher in Wistar HCQ animals but not in hypertensive ones. HCQ increased lipid peroxidation levels and the activity of SOD, CAT, and glutathione peroxidase in both Wistar and SHR rats. Treatment also reduced perivascular collagen in Wistar and interstitial collagen in SHR. HCQ reduced the immunohistochemical labeling for interleukin-1 beta (IL-1β) in the cardiac tissue of normotensive and hypertensive rats. HCQ reduced mesenteric, retroperitoneal, and epididymal fat mass in normotensive animals but not in hypertensive ones. Liver and pancreas weights were not affected by HCQ in either strain. Thus, it can be concluded that HCQ treatment affects the metabolic profile and cardiac morphology differently between normotensive and hypertensive animals. Notably, HCQ demonstrated better benefits in SHR, promoting greater protective effects against hypertrophy, cardiac fibrosis, and oxidative stress.